2014
DOI: 10.1007/s11418-014-0840-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neuroprotective effect of chrysin via modulation of endogenous biomarkers in a rat model of spinal cord injury

Abstract: The objective of the present investigation was to evaluate the neuroprotective efficacy of chrysin in an experimental rat model of spinal cord injury (SCI). SCI was induced in male Sprague-Dawley rats by placing an aneurysm clip extradurally for 60 s at T10. The rats received treatment with either vehicle (SCI control) or chrysin (10, 20 and 40 mg/kg, p.o.) for 28 days. The various behavioral, biochemical and molecular parameters were determined. Chronic treatment with chrysin (20 and 40 mg/kg) significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 67 publications
3
41
0
1
Order By: Relevance
“…20,[31][32][33] Briefly, single-stranded cDNA was synthesized from 5 lg of total cellular RNA using reverse transcriptase (MP Biomedicals India Private Limited, India) as described previously. 20 Amplification of b-actin served as a control for sample loading and integrity. The primer sequences for KIM-1, NGAL, NF-kB, Bcl-2, and bactin were selected according to the previously reported method 15 (Supplementary material).…”
Section: -30mentioning
confidence: 99%
“…20,[31][32][33] Briefly, single-stranded cDNA was synthesized from 5 lg of total cellular RNA using reverse transcriptase (MP Biomedicals India Private Limited, India) as described previously. 20 Amplification of b-actin served as a control for sample loading and integrity. The primer sequences for KIM-1, NGAL, NF-kB, Bcl-2, and bactin were selected according to the previously reported method 15 (Supplementary material).…”
Section: -30mentioning
confidence: 99%
“…The levels of mRNA were analyzed in skin tissue using a reverse transcription (RT)-PCR approach as described previously (Kandhare et al, 2014b;Visnagri et al, 2014). The primer sequences for tumor necrosis factor-a (TNF-a), interleukin-1 beta (IL-1b), IL-6, IL-8, smad-3, smad-7, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-jB), vascular endothelial growth factor (VEGF), pol g, transforming growth factor-beta (TGF-b), Bcl-2-associated X protein (BAX), and b-actin are presented in Table 1.…”
Section: Myeloperoxidase Activitymentioning
confidence: 99%
“…The levels of mRNA were analyzed in skin tissue using a RT-PCR approach as described previously (Kandhare et al, 2014b;Visnagri et al, 2014). The primer sequences for collagen-1 and b-actin are presented in Table 1.…”
Section: Determination Of Collagen-1 By Reverse Transcriptase Pcr In mentioning
confidence: 99%
“…Chrysin (5,7-dihydroxyflavone) is a flavonoid that is widely present in honey, propolis, and plant extracts (Ahad et al, 2014;Kandhare et al, 2014;Pietta, 2000). A bulk of studies have shown that chrysin possesses diverse pharmacological activities including antivirus (Wang et al, 2014), antioxidant (Sultana et al, 2012), anti-tumor (Yu et al, 2013b), anxiolytic (Zanoli et al, 2000), neuroprotection (Kandhare et al, 2014), and anti-diabetes (Ahad et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A bulk of studies have shown that chrysin possesses diverse pharmacological activities including antivirus (Wang et al, 2014), antioxidant (Sultana et al, 2012), anti-tumor (Yu et al, 2013b), anxiolytic (Zanoli et al, 2000), neuroprotection (Kandhare et al, 2014), and anti-diabetes (Ahad et al, 2014;Li et al, 2014). Various mechanisms are involved in chrysinmediated health benefits such as attenuation of inflammation (Rehman et al, 2013), alleviation of oxidative stress (Mantawy et al, 2014), and induction of cell cycle arrest and apoptosis (Rashid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%